The supervised internship: lines, challenges, movements and possibilities of formation - Furtado Ribeiro, Luis Távora (2017)
It is discussed here the supervised internship as a process that should allow interns to make constant use of dialogue, of inquiring and of reflection over the constructed and under construction experiences, abilities, attitudes and knowledge, aiming always to provide meaning to the apprehend apprenticeship from this process. Based on relevant researches and essays regarding the theme, it is aimed here to highlight the experience of the internship as a continuum and dynamic process of apprenticeship regarding the teaching profession, as well as its relations with the several territories and times and, even so, the ways of being, doing and laying in the profession. It is concluded highlighting the value of living the experience of the internship anchoring in a critic-reflexive perspective, as well as the significance of the participation, the interest and the intern to maintain an active posture in the activities performed in the internship.